2014
DOI: 10.9753/icce.v34.sediment.87
|View full text |Cite
|
Sign up to set email alerts
|

Impact of an Offshore Wind Farm on Wave Conditions and Shoreline Development

Abstract: The influence of offshore wind farms on the wave conditions and impact on shoreline development is studied in a generic set-up of a coast and a shoreline. The objective was to estimate the impact of a typical sized offshore wind farm on a shoreline in a high wave energetic environment. Especially the shoreline's sensitivity to the distance from the OWF to the shoreline was studied. The effect of the reduced wind speed inside and on the lee side of the offshore wind farm was incorporated in a parameterized way … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…A modeling experiment showed that the wave height could easily be reduced in the order of 4-5% 2 km down-wind of the OWF and up to 2% 10 km down-wind. The direction of the incoming waves is also modified [38]. The lee effects of the OWF result in sediment accumulations similar to what can be seen behind shore parallel offshore breakwaters.…”
Section: Wake and Lee Effectsmentioning
confidence: 81%
“…A modeling experiment showed that the wave height could easily be reduced in the order of 4-5% 2 km down-wind of the OWF and up to 2% 10 km down-wind. The direction of the incoming waves is also modified [38]. The lee effects of the OWF result in sediment accumulations similar to what can be seen behind shore parallel offshore breakwaters.…”
Section: Wake and Lee Effectsmentioning
confidence: 81%
“…Therefore, the momentum flux which would reach the shore, should be different from that if the wind farm were not present. This is certainly an important finding, not much cited in the literature regarding environmental impact assessments of wind farms (Christensen et al, 2014), with the advantage that the method herein described in this paper provides an objective way of computing the overall effect of a wind farm on the wave field, through the computation of the modified field of the radiation stress tensor.…”
Section: Radiation Stressmentioning
confidence: 82%
“…In this study, the computer program WAMIT  (WaveAnalysisMIT) is used to solve the diffraction boundary value problem to obtain the time harmonic solutions of the first term of the series expansion for a specific incident wave field. WAMIT  has been widely used in the offshore and naval industry, but it has also been adopted in some recent studies to the case of vertical cylinders in the field of coastal engineering and studies of wind farms (Christensen et al, 2014;Newman, 2014;Mohseni et al, 2018;Read et al, 2018).…”
Section: Wave-cylinder Diffractionmentioning
confidence: 99%